The electromagnetic origin of gravity (International Journal of Scientific Research and Management (IJSRM), 2023)
Under the condition of the expansion of the universe and all masses with their charges in it, the electromagnetic origin of the gravitational force is determined with the help of the Lorentz force. Basic physical relations to the interactions of the basic forces of nature are established. This includes calculation formulas for the gravitational constant, the proton radius and the age of the universe.